2010
DOI: 10.1108/00242531011065127
|View full text |Cite
|
Sign up to set email alerts
|

Information‐seeking behavior of the social sciences faculty at Kuwait University

Abstract: Purpose -The purpose of this paper is to investigate the information-seeking behavior of the social sciences faculty at Kuwait University. Design/methodology/approach -A survey method was used for this study. The data were collected using a structured, peer-reviewed questionnaire self-administered to 77 faculty members, with 54 returns. Findings -It was found that these respondents heavily depend on books and journals for teaching and on a larger variety of materials for research purposes. Their use of informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The questionnaire showed that only 25.24% of the participants were using the English language to find information, while 79.76% were using the Arabic language to find information. The results were consistent with the literature as previous studies indicated that the English language is an obstacle for many researchers in the Arab regions (Al-Wreikat et al, 2015;Elgllab & Shehata, 2017;Marouf & Anwar, 2010).…”
Section: Citing Information Sourcessupporting
confidence: 92%
“…The questionnaire showed that only 25.24% of the participants were using the English language to find information, while 79.76% were using the Arabic language to find information. The results were consistent with the literature as previous studies indicated that the English language is an obstacle for many researchers in the Arab regions (Al-Wreikat et al, 2015;Elgllab & Shehata, 2017;Marouf & Anwar, 2010).…”
Section: Citing Information Sourcessupporting
confidence: 92%
“…Active usage of information resources by the professoriate are found to differ across academic discipline, age, geographical boundaries, context (e.g. teaching, research) and individual orientation and disposition towards information resources (Hemminger et al 2007;Marouf & Anwar 2010;Nwone & Mutula 2018;Rupp-Serrano & Robbins 2013;Singh & Satija 2007;Xuemei 2010). Generally, social science professors use electronic resources more than their counterparts in humanities, preferring electronic resources for research and print resources for teaching (Xuemei 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Nigeria and for this study, the professoriate comprises the readers (assistant professors), associate professors and professors of a university. Laila and Mumtaz (2010) observed that faculty members, especially at the professoriate level, heavily depend on books, journals, conferences, subject experts and colleagues to meet their information needs. Recent studies, however, show a change in behaviour towards acceptance and use of electronic resources by the professoriate, because of the prevalence of World Wide Web, search engines, online databases, e-journals, e-books, e-mails, online catalogues and web portals that have altered usage behaviour (Nwone & Mutula 2018).…”
Section: Introductionmentioning
confidence: 99%